Development of Education-Based Interpretation Activities at The City Museum in Makassar: Pengembanagan Kegiatan Interpretasi Berbasis Edukasi Di Museum Kota Makassar - Muhammad Arya Jamaluddin; Buntu Marannu Eppang; Darmayasa Darmayasa (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
A museum is a place to store items that represent the culture of the ancestors that are believed in. Interesting activities held at the museum so that tourists can gain new experiences and not feel bored while visiting the museum for tourism activities. This research aims to: (1) identify the potential tourist attractions at the City Museum in Makassar before organizing activities there, and (2) develop more engaging activities in the museum by enhancing interpretive activities at the City Museum in Makassar. Data collection for this research was conducted using techniques: interviews and documentation, applying the R&D (Research and Development) method with a development model in accordance with Sugiyono. The results of this research show that (1) the potential of the Makassar City Museum is very large, with hundreds of historical collections displayed in various exhibition spaces of the museum. This museum has great potential for tourists who want to learn more about the city of Makassar, and (2) the development of educational-based interpretive activities at the Makassar City Museum is structured based on interview results, where the components are created in accordance with recommendations from the management of the Makassar City Museum, which is certainly in line with the concept of information presentation, namely storytelling, and is reinforced with games that have been tailored to the characteristics of tourist attractions. It is hoped that this interpretative product can serve as a reference for tourism operators who wish to package educational and enjoyable interpretative programs at the Makassar City Museum, as well as a resource for museum managers in providing experiences to tourists through this interpretative product.